Degradation reduces the diversity of nitrogen-fixing bacteria in the alpine wetland on the Qinghai-Tibet Plateau - Li, Chengyi; Li, Xilai; Yang, Yuanwu; Shi, Yan; Li, Honglin (Frontiers in Plant Science, 2022)
Biological nitrogen fixation is a key process in the nitrogen cycle and the main source of soil available nitrogen. The number and diversity of nitrogen-fixing bacteria directly reflect the efficiency of soil nitrogen fixation. Alpine wetland on the Qinghai-Tibet Plateau (QTP) is degrading increasingly, with a succession towards alpine meadow. Significant changes in soil physicochemical properties accompany this process. However, it is unclear how the soil nitrogen-fixing bacteria during the degradation and its relationship with soil physicochemical properties change and what processes happened. In this study, the nifH gene was used as a molecular marker to further investigate the diversity of nitrogen-fixing bacteria at different stages of the degradation (none, light and severe degeneration) in alpine wetland. The results showed that wetland degradation significantly reduced the diversity, altered the community composition of nitrogen-fixing bacteria, decreased the relative abundance of Proteobacteria, and increased the relative abundance of Actinobacteria. In addition to the dominant phylum, the class, order, family, and genus of nitrogen-fixing bacteria had significant changed in relative abundance. Analysis of Mantel test showed that pH, soil water content (SWC), the organic carbon (TOC), total nitrogen (TN), soil C:P ratio and abundance had a significant positive correlation. TOC, TN, total phosphorus (TP), soil C:P ratio and Shannon had a significant positive correlation. The RDA ranking further revealed that TOC, SWC and TN were the main environmental factors influencing the community composition of nitrogen-fixing bacteria. It is found that the degradation of alpine wetland inhibited the growth of nitrogen-fixing bacteria to a certain extent, leading to the decline of their nitrogen-fixing function.